Investigation of fatty acids in Camelina microcarpa Andrz - Lisova, T. O.; Trzhetsynskyi, S. D.; Kinichenko, A. O.; Лісова, Тетяна Олександрівна; Тржецинський, Сергій Дмитрович; Кініченко, Анна Олександрівна (My University, 2025)
Actuality. The available literature lacks information on the fatty acid content in the aerial parts of Camelina microcarpa grown in Ukraine. The aim of the study is to analyze the fatty acid composition of the herb and seeds of Camelina microcarpa Andrz. Material and methods. Raw material was cultivated and harvested in Zaporizhzhia region (Ukraine) in 2018. Seeds for cultivation were provided by the National Center for Plant Genetic Resources of Ukraine. Fatty acid composition was analyzed using a gas chromatograph (Agilent 7890B GC System) with a mass spectrometric detector (Agilent 5977B GC/MSD) and a DB-5ms column. Research results. A total of 11 fatty acids were identified: 4 in the herb and 11 in the seeds. The total fatty acid content was 3,58% in the herb and 44,24% in the seeds. Saturated fatty acids predominated in the herb, while unsaturated fatty acids dominated in the seeds. The proportion of unsaturated fatty acids in the herb was 35,98%, with α-linolenic acid (27,34%) being the most abundant. In the seeds, unsaturated fatty acids (87,47%) significantly exceeded saturated acids, with α-linolenic acid (39,09%) as the dominant component. Linoleic, α-linolenic, palmitic, and arachidic acids were common in both the herb and seeds. Conclusion. Camelina microcarpa Andrz. seeds are a promising plant-based source of polyunsaturated fatty acids for pharmaceutical applications. Актуальність. У доступних джерелах літератури відсутня інформація щодо вмісту жирних кислот у надземній частині Camelina microcarpa, вирощеного в Україні. Мета дослідження – провести аналіз жирнокислотного складу трави та насіння Camelina microcarpa Andrz. Матеріал і методи. Сировину культивували та збирали в Запорізькій області (Україна) у 2018 році. Насіння для культивування було надане Національним центром генетичних ресурсів рослин України. Жирнокислотний склад аналізували методом газової хроматографії (Agilent 7890B GC System) з мас-спектрометричним детектором (Agilent 5977B GC/MSD) та колонкою DB-5ms. Результати дослідження. Виявлено загалом 11 жирних кислот: 4 у траві й 11 у насінні. Загальний вміст жирних кислот становив 3,58% у траві та 44,24% у насінні. У траві переважали насичені жирні кислоти, тоді як у насінні домінували ненасичені. Частка ненасичених жирних кислот у траві становила 35,98%, із яких α-ліноленова кислота (27,34%) була найбільш поширеною. У насінні вміст ненасичених жирних кислот (87,47%) значно перевищував насичені, до того ж α-ліноленова кислота (39,09%) була основним компонентом. Лінолева, α-ліноленова, пальмітинова й арахідонова кислоти були спільними для трави та насіння. Висновок. Насіння Camelina microcarpa Andrz. є перспективним рослинним джерелом поліненасичених жирних кислот для фармацевтичного застосування.
Дослідження жирних кислот у Camelina microcarpa Andrz
Keywords: Camelina microcarpa Andrz.; herb; seeds; fatty acids; GC-MS; трава; насіння; жирні кислоти; ГХ-МС